DEVELOPING STUDENT’S ENGLISH LITERACY SKILLS THROUGH KAMPUS MENGAJAR PROGRAM DEVELOPING STUDENT’S ENGLISH LITERACY SKILLS THROUGH KAMPUS MENGAJAR PROGRAM - Ridha Mardalena; Rahmat Nasrullah; Faridawati Faridawati (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This study explores the development of students' English literacy skills through the Kampus Mengajar Program as part of the Merdeka Belajar Kampus Merdeka (MBKM) policy. The program aims to enhance students' reading, writing, listening, and speaking abilities by engaging preservice teachers as learning facilitators in elementary schools. A descriptive qualitative research method was employed, involving six English Education students from Muhammadiyah University of Kendari who taught in six elementary schools. The findings reveal the implementation of various innovative strategies, including a 15-minute book reading session before class, digital learning through applications like Duolingo, and speaking activities involving discussions and role-playing. This approach gradually improved students’ vocabulary comprehension, speaking fluency, and listening skills. The program also benefits preservice teachers by enhancing their teaching experience and understanding of effective language learning strategies. In conclusion, the Kampus Mengajar Program significantly contributes to improving students’ English literacy through technology-based and interactive learning methods, creating a more engaging and effective learning environment.